Intraindividual relationships between training loads and heart-rate variability in high-level female futsal players: A longitudinal study - Nakamura, F. Y.; Costa, J. A.; Travassos, B.; Ortuño, D.; Pino-Ortega, J. (International Journal of Sports Physiology and Performance, 2023)
Purpose: To investigate the internal training loads of a professional Spanish female futsal team throughout 26 weeks of training including preseason and in-season weeks and verify the impact of training period and/or training load magnitudes on heart-rate variability responses. Furthermore, we aimed to assess, intraindividually, the relationship between training load and the coefficient of variation (CV) of weekly natural log of the root mean square difference of successive normal interbeat (RR) intervals (lnRMSSDCV), obtained from ~5 measures per week, and recorded in the seated position.